Al-Mushtarâk al-Lafdhî (Homonimi) dalam Bahasa Arab; Suatu Kajian Semantik - Baiq Tuhfatul Unsi (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2013)
Al-Mushtarâk al-Lafz?î (homonymy) are some of the same word, both written and pronunciation form, but has different meaning. For example, the word can mean snake venom is berhomonimi words that can mean up to it, can. In Arabic, the word (???) can significantly towards the west (?????) and also significantly bucket (?????). Another example, the word (????) has three meanings, namely: (1) the father of the father/mother ??? ????) / ??? ????), (2) part, good fortune (???? - ?????), (3) the banks of the river (???? ?????). Homonym (al-mushtarâk al-lafz?î) in Arabic, not only in the words, but also can occur in a sentence. In a scientific study balaghah, homonym is called the Jinas, the similarity of two different words meaning. In other words, a word that used in different places and have different meaning. In general, al-jinâs divided into two kinds, namely: jinâs tâm and jinâs ghairu tâm. A good understanding of the homonymy of language, especially Arabic to avoid ambiguity and distortion of the message contained in the utterance or sentence.